Structural and thermal characterization of multiwall carbon nanotubes (MWCNTs) / aluminum (Al) nanocomposites. (15th October 2018) - Saadallah, S.; Cablé, A.; Hamamda, S.; Chetehouna, K.; Sahli, M.; Boubertakh, A.; Revo, S.; Gascoin, N.
Abstract: The present study aims to assess the influence of multiwall carbon nanotubes (MWCNTs) as a filler in an Aluminum (Al) matrix in terms of structural and thermal performance. Al + 1% MWCNTs nanocomposites were prepared, and their structural behavior was characterized using dilatometry, X-ray diffraction (XRD), infrared (FT-IR) and Raman spectroscopy as compared to Al + 0% MWCNTs samples. The dilatometry measurements confirmed an important reduction of the thermal dilatation coefficient, while Raman spectroscopy allowed to report an increase of defects. The thermal stability of the composites were then assessed using differential scanning calorimetry (DSC) and thermo-gravimetric analysis (TGA). The obtained results confirmed the impact of the MWCNTs on the physico-chemical characteristics of Al-MWCNTs nanocomposites, and in particular on the improvement of the thermal properties (increased thermal resistance) as compared to pure aluminum, indicating potential applications in the aeronautical, transport and construction sectors. Graphical abstract: Image 1